2015
DOI: 10.1039/c5tc02195b
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and flash memory behavior of alternate copolymer containing carbazole donor and perylenediimide derivatives acceptor by the hybridization of organo-silicon

Abstract: In this study, two new donor-acceptor alternate copolysiloxanes containing carbazole and PDI derivatives pendants (PCzMSi-alt-PDISi and PCzPhSi-alt-PDISi) were prepared. The two copolysiloxanes showed the resistor type memory behavior. The memory devices based on PCzMSi-alt-PDISi and PCzPhSi-alt-PDISi exhibited nonvolatile flash memory characteristics, with an ON/OFF current density ratio of 10 3 and low threshold voltages (less than 1 V). As far as we know, it is the first nonvolatile flash memory device repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
See 1 more Smart Citation
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
“…Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra‐low power memory devices during their practical 3D integration . To date, enormous efforts have been devoted to the rational design of memristive materials and their property studies, especially the achievement of Flash, write‐once‐read‐many times (WORM), and dynamic random access memory (DRAM) memory effect . However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously .…”
supporting
confidence: 65%
“…It is understood that the charges inject into the memory layer will induce a countering space charge field, screen the applied external electric field, and inhibit further charge injection into the active layer. [50,51] Therefore, PIs with 6FDA could perform a less hindered charge conduction with a higher I on /I off during the trap filling regime with I ∼ V m+1 (m > 1). This result indicates the energy barrier between HOMO level of PIs and work function of Al electrode plays an important role in the hole trapping to fulfill a smooth transition from the OFF state to the ON state.…”
Section: Flexible Resistive Memory Devices Characterizationmentioning
confidence: 99%
“…Unlike classical memristor-based nonvolatile memory devices, which show good switching endurance, [35][36][37][38] completely different switching characteristics were found when a series of voltage sweep cycles (3→−5→3 V) were sequentially applied to our device. Even though a repeatable resistanceswitching could be observed under both positive and negative bias voltages during the following voltage sweeps, the measured current at the high-resistance state continually increased with increasing number of scans.…”
Section: Doi: 101002/adma201602890mentioning
confidence: 98%